Scenario of commercial mushroom production in Nagaland - Giriyappa, Rajesha; Bendangsenla; Singh, Mahak; Seyie, Azeze; Rajkhowa, D. J. (Mushroom Research, 2022)
The Nagaland state is having a large scope for mushroom production due to prevalence of suitable weather condition, raw materials and presence of 100% mushroom eater. The mushroom production enterprise is a profitable venture in Nagaland due to high demand for consumption. The prevalence of weather is very well suited for the oyster and shiitake mushroom cultivation in a larger area of Nagaland whereas paddy straw and milky mushroom cultivation is limited to the few district of Nagaland. Even though prevailing weather was suitable in Nagaland; production of mushroom is very limited. The ICAR Research Complex for NEH Region, Nagaland Centre, Medziphema is imparting the training and demonstration of mushroom cultivation for the interested farmers under various schemes and programmes. By understanding the scope and opportunities in mushroom, many progressive farmers are interested and started the commercial cultivation in Nagaland mitigate mushroom demand in Nagaland.